Clinical, methodology, and patient/carer expert advice in pediatric drug development by conect4children - Katharine Cheng; Fenna Mahler; Irja Lutsar; Begonya Nafria Escalera; Stefanie Breitenstein; Gilles Vassal; Joana Claverol; Nuria Noel Palacio; Ron Portman; Gavin Pope; Martijn Bakker; Tessa van derGeest; et al. (Wiley, 2023)
Abstract Many medicines are used "off‐label" in children outside the terms of the license. Feasible pediatric clinical trials are a challenge to design. Conect4children (c4c) is an Innovative Medicines Initiative project to set up a pan‐European pediatric clinical trial network aiming to facilitate the development of new medicines for children. To optimize pediatric trial development by promoting innovative trial design, c4c set up a European multidisciplinary advice service, including the voice of young patients and families, tailored to industry and academia. A network of experts was established to provide multidisciplinary advice to trial sponsors. Experts were selected to join clinical and innovative methodology expert groups. A patient and public involvement (PPI) database, to include the expert opinion of patients and parents/carers was formed. A stepwise process was developed: (1) sponsors contact c4c, (2) scoping interview takes place, (3) ad hoc advice group formed, (5) advice meeting held, and (6) advice report provided. Feedback on the process was collected. Twenty‐four clinical and innovative methodology expert groups (>400 experts) and a PPI database of 135 registrants were established. As of September 30, 2022, 36 advice requests were received, with 25 requests completed. Clinical and methodology experts and PPI representatives participated in several advice requests. Sponsors appreciated the advice quality and the multidisciplinary experts from different countries, including experts not known before. Experts and PPI participants were generally satisfied with the process. The c4c project has shown successful proof of concept for a service that presents a new framework to plan innovative and feasible pediatric trials.